Clearing of euro OTC derivatives post Brexit: An analysis of the present cost estimates - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
In the context of the upcoming Brexit, a relocation of the clearing of euro-OTC derivatives for EU-based firms is the subject of controversial discussion. The opponents of a relocation argue that a relocation would cause additional costs for market participants of up to USD 100 bn over a period of 5 years. This paper shows that this cost estimate is fairly unrealistic and that relocation costs would amount to approximately USD 0.6 bn p.a., which translates to cumulative costs of around USD 3.2 bn for a transition period of 5 years. In light of the strategic importance of systemically relevant CCPs for the financial stability of the eurozone, the potential relocation costs should not be a decision criterion. – – Im Zusammenhang mit dem Brexit wird über die Kosten einer Relokation des Clearing des Euro-OTC-Derivate-Geschäftes auf ein EU-CCP diskutiert. Das vorliegende Papier zeigt, dass die bislang vorliegenden Kostenschätzungen, die von Kosten in Höhe von bis zu USD 100 Mrd. für einen Zeitraum von fünf Jahren ausgehen, viel zu hoch sind. Die erwarteten Kosten einer Relokation liegen vielmehr bei ca. USD 0,6 Mrd. p.a. bzw. ca. USD 3,2 Mrd. für eine Übergangsphase von fünf Jahren. Angesichts der hohen Bedeutung von systemrelevanten CCPs für die Stabilität der Eurozone sollten diese Kosten nicht entscheidungsrelevant für eine Relokation sein.
urn:nbn:de:hebis:30:3-437387
Keywords: G20; G21; 330